Measurement of the Postgraduate Educational Environment of Junior Doctors Training in Medicine at an Irish University Teaching Hospital. (August 2016) - Flaherty, G.; Connolly, R.; O'Brien, T.
Abstract Background A positive learning environment in which postgraduate doctors are supported, supervised and nurtured, is likely to lead to enhanced professional satisfaction and improved patient care. Aims The aims of the current study were to use the PHEEM inventory to determine the aspects of their current learning environment which junior doctors rate most and least positively. Methods The PHEEM questionnaire was administered to all junior doctors working in medical subspecialties at Galway University Hospitals in Ireland. A response rate of 60 % (n  = 61) was obtained. Results The mean total PHEEM score was 82.88 ± 18.99, corresponding to an educational environment with more positive than negative aspects but with room for improvement. The mean total PHEEM score (±standard deviation) of registrars (89.65 ± 20.92) exceeded that of Interns (84.00 ± 15.26) and SHOs (75.12 ± 18.09). Over half (55 %) of the individual items were rated by the junior doctors as more positive than negative. Nineteen items (48 %) pointed to areas in need of enhancement, whilst 3 items were rated as satisfactory or better. Analysis of qualitative data confirmed that deficiencies exist in various aspects of the educational climate, including protected educational time, access to suitable learning opportunities, the nature of tasks performed by junior doctors, the hospital bleep protocol, implementation of the European Working Time Directive, feedback and career guidance. Conclusions Recommendations stemming from this study should lead to improvements in the quality of the educational environment of junior doctors and may stimulate similar evaluations in other teaching hospitals.